Membangun Kehidupan Komunitas Umat melalui Etika Dekalog: Kajian Teologi Konstruktif Keluaran 20:1–17 - Maria Evvy Yanti; Periadi Ezekiel Soala Ritonga (Immanuel: Jurnal Teologi dan Pendidikan Kristen, 2026)
Recent archaeological findings about the relationship between Israel and its exclusivism among other nations need to be examined with the history of the nation's pluralism. The origins of the nation of Israel seem to have influenced the various contexts of life (religious, social, economic, political and legal) that occurred in the midst of pluralism. The context of Israel's life recorded in the Decalogue (Exodus 20:1-17) was formed by the process of assimilation and adaptation of various elements of the surrounding Canaanite culture and religion. It needs to be examined to look at the universal theological values of Decalogues from different eras and contexts. The relevance of these theological values for contextual missions as an effort to build a plural common life. Decalogue can be used as a reference text and theological construction of harmony in the midst of the plurality. Qualitative type research is carried out in this paper through the redaction of social history of the text of the formation of Decalogue values. While this type of descriptive research is used to analyze the implementation of contextual missions based on Decalogue values. This paper shows that the theological values of Decalogue contribute to the contextual religious communities